2008
DOI: 10.1016/j.ejcts.2008.05.010
|View full text |Cite
|
Sign up to set email alerts
|

The effect of off-pump coronary artery bypass grafting on platelet activation in patients on aspirin therapy until surgery day☆

Abstract: Aspirin therapy continued until surgery day does not protect against acute platelet activation in patients after OPCAB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 26 publications
2
6
0
1
Order By: Relevance
“…Early administration of clopidogrel seems to play a key role as over-reactivity of platelets due to surgical trauma which occurs shortly after surgery and its suppression with a high dose of aspirin (300 mg 48 hours after chest closure) is not effective. Those results were published by authors elsewhere [14]. The hypercoagulation phenomenon is strongly expressed in patients who were operated with off-pump technique [15].…”
Section: Discussionsupporting
confidence: 69%
“…Early administration of clopidogrel seems to play a key role as over-reactivity of platelets due to surgical trauma which occurs shortly after surgery and its suppression with a high dose of aspirin (300 mg 48 hours after chest closure) is not effective. Those results were published by authors elsewhere [14]. The hypercoagulation phenomenon is strongly expressed in patients who were operated with off-pump technique [15].…”
Section: Discussionsupporting
confidence: 69%
“…However, both of these studies are limited by their retrospective nature. In a prospective observational clinical study, Suwalski et al [27] investigated the effect of preoperative aspirin use with a myocardial enzyme and platelet function analyzer (PFA-100 ® ; Dade Behring, Germany). Their findings suggested that preoperative aspirin use did not protect against acute platelet activation in OPCAB.…”
Section: Discussionmentioning
confidence: 99%
“…This affects final clinical outcome of treatment as patients undergoing re-exploration due to postoperative bleeding have higher mortality and longer hospitalization [1,4,5]. To achieve reliable results we eliminated two risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…Wykonano również regresję logistyczną, w której mierzalnym parametrem był drenaż krwi w pierwszej dobie po operacji. Za istotne statystycznie uznano parametry, których p było niższe od 0,05. www.journals.viamedica.pl/folia_cardiologica Ireneusz Haponiuk, Komentarz analiza danych dotyczących tak powszechnego czynnika ryzyka krwawień pooperacyjnych, jakim jest standardowe leczenie kwasem acetylosalicylowym u pacjentów z przewlekłą chorobą wieńcową, jak należy sądzić, także w badanej grupie [5].…”
Section: Streszczenieunclassified
See 1 more Smart Citation